Cinnamaldehyde Inhibits Staphylococcus aureus Virulence Factors and Protects against Infection in a Galleria mellonella Model - Ferro, Thiago A. F.; Araújo, Jéssica M. M.; dos Santos Pinto, Bruna L.; dos Santos, Jéssica S.; Souza, Eliene B.; da Silva, Bruna L. R.; Colares, Valderlane L. P.; Novais, Tânia M. G.; Filho, Clovis M. B.; Struve, Carsten; Calixto, João B.; Monteiro-Neto, Valério; et al. (Frontiers in Microbiology, 2016)
Bacterial resistance to the available marketed drugs has prompted the search of novel therapies; especially in regards of anti-virulence strategies that aim to make bacteria less pathogenic and/or decrease their probability to become resistant to therapy. Cinnamaldehyde is widely known for its antibacterial properties through mechanisms that include the interaction of this compound with bacterial cell walls. However, only a handful of studies have addressed its effects on bacterial virulence, especially when tested at sub-inhibitory concentrations. Herein, we show for the first time that cinnamaldehyde is bactericidal against Staphylococcus aureus and Enterococcus faecalis multidrug resistant strains and does not promote bacterial tolerance. Cinnamaldehyde actions were stronger on S. aureus as it was able to inhibit its haemolytic activity on human erythrocytes and reduce its adherence to latex. Furthermore, cinnamaldehyde enhanced the serum-dependent lysis of S. aureus. In vivo testing of cinnamaldehyde in Galleria mellonella larvae infected with S. aureus, showed this compound improves larvae survival whilst diminishing bacterial load in their hemolymph. We suggest that cinnamaldehyde may represent an alternative therapy to control S. aureus-induced bacterial infections as it presents the ability to reduce bacterial virulence/survival without promoting an adaptive phenotype.